Phenotypic and Genotypic Analysis of the Population of Phytophthora infestans in Bangladesh Between 2014 and 2019 - Islam, M.H.; Shanta, S.S.; Hossain, M.A.; Rahaman, E.H.M.S.; Al Mahmud, A.; Akhond, M.A.Y.; Sullivan, L.; Cooke, D.E.L.; Kessel, G.J.T.; Cooke, L.R.; Islam, M.R. (Springer, 2023)
In Bangladesh, the third largest producer of potatoes in Asia, late blight, caused by Phytophthora infestans, is the major constraint to production. Nevertheless, there is a lack of published information on the pathogen population. A collection of 69 isolates obtained from samples of infected potato foliage collected in 2018–2019 varied significantly in their aggressiveness to detached potato leaflets and tuber slices of cv. Diamant. On leaflets, most isolates were highly aggressive, colonizing more than half the surface in 7 days. On tuber slices, while some isolates were highly aggressive, those collected in 2019 were less so. There was a significant effect of the locations from which the isolates were obtained on aggressiveness to both leaflets and tuber slices, but aggressiveness to leaflets and to tuber slices was not significantly correlated. All isolates were A2 mating type and either intermediate (38%) or resistant (62%) in sensitivity to the fungicide metalaxyl. A subset of 24 isolates all had mitochondrial DNA haplotype Ia.